Effect of Cell Lysis (CLs) Products on Acidophilic Chemolithotrophic Microorganisms and the Role of Acidocella Species - Vardanyan, Arevik; Achilleos, P.; Kafa, Nasia; Papadopoulou, M.; Vardanyan, Narine S.; Vyrides, Ioannis (My University, 2017)
Acidophilic chemolithotrophic microorganisms (CMs) are widely used for bioleaching of mineral resources. However, the growth of bacteria and their leaching activity are often inhibited (restricted) by organic components, e.g. lysates and exudates. The aims of this study were to examine the extent of cell lysis (CLs) inhibition on acidophilic microorganisms and to identify microorganisms that can utilize CLs products and eliminate their inhibition effect on acidophilic microorganisms. Specifically, it was revealed that Acidithiobacillus caldus was severely inhibited at 5% CLs products, whereas A. ferrooxidans and Leptospirillum ferriphilum are severely inhibited at 20%. It has been found that strains RBA and RBB of heterotrophic bacteria, isolated from anaerobic sludge, can biodegrade CLs products and when co-cultured with A. ferrooxidans, they can alleviate the toxic effect of CLs products under low pH (2–3). It has been shown that besides CLs, isolated strains can grow on glucose, glycerol, yeast extract, citric acid, and tryptone soya broth with an optimum temperature of 35°C and a pH of 3. The strains showed the ability to reduce ferric ions to ferrous ions when glycerol was used as a substrate after 2 days under both aerobic and anaerobic conditions. On the basis of morphophysiological and molecular biological studies, the isolated strains RBA and RBB were identified as Acidocella spp.
Keywords: Acidocella; Biodegradation; Cell lysis; Chemolithotrophic microorganisms; Heterotrophic microorganisms